Smart School Sebagai Sarana Informasi Sekolah di SDIT Ibnu Khaldun Cirebon - Ade Bani Riyan; Dwi Teguh Afandi; Tuti Hartati; Dita Rizki Amalia; Odi Nurdiawan (JURIKOM (Jurnal Riset Komputer), 2021)
The need for information in the world of education in this modern era is very important in determining the progress of an institution. By implementing and utilizing information technology can facilitate school institutions in organizing data and will produce a database file that will make it easier for users to access data. However, the use of information technology at SDIT Ibnu Khaldun Cirebon has not been used optimally. This is where the author's desire to create a Smart School application emerged, which is an application that functions as an academic information application to support daily activities at the school.This study aims to improve the quality of schools and meet the needs of schools and parents in disseminating general school information, and student academic information at SDIT Ibnu Khaldun Cirebon.The method used in this research is the research and development method. Data collection techniques in this study using interviews. This research was conducted at SDIT Ibnu Khaldun by involving teachers, principals, students, and parents of students as research subjects.Based on the results of testing with the black box method on the Smart School application, it can be concluded that functionally it produces results that are in line with expectations